2018
DOI: 10.1159/000489439
|View full text |Cite
|
Sign up to set email alerts
|

Dioleoylphosphoethanolamine Retains Cell Surface GLUT4 by Inhibiting PKCα-Driven Internalization

Abstract: Background/Aims: Phosphatidylethanolamine, a component of the plasma membrane, regulates diverse cellular processes. The present study investigated the role of 1,2-dioleoyl-sn-glycero-3-phosphoethanolamine (DOPE) in the trafficking of the glucose transporter GLUT4 and the glucose homeostasis. Methods: Monitoring of GLUT4 trafficking, GLUT4 internalization assay, and glucose uptake assay were carried out using differentiated 3T3-L1-GLUT4myc adipocytes. Akt1/2 and PKC isozymes were knocked-down by transfecting e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The PKCα inhibitor dioleoyl phosphoethanolamine retained cell surface GLUT4 by inhibiting PKCα-driven internalization in adipocytes. PKC β and λ were involved in the insulin signaling cascade causing PKC-meditated GLUT4 traffic in skeletal muscle cells [ 19 , 51 ]. When we studied which of the three signaling pathways was/were involved in FSE-mediated glucose uptake, we found that both Compound C and Gö6983 remarkably inhibited the promotion by FSE of GLUT4 translocation and expression, but the inhibition effect of Wortmannin was relatively weak ( Figure 4 A,B).…”
Section: Discussionmentioning
confidence: 99%
“…The PKCα inhibitor dioleoyl phosphoethanolamine retained cell surface GLUT4 by inhibiting PKCα-driven internalization in adipocytes. PKC β and λ were involved in the insulin signaling cascade causing PKC-meditated GLUT4 traffic in skeletal muscle cells [ 19 , 51 ]. When we studied which of the three signaling pathways was/were involved in FSE-mediated glucose uptake, we found that both Compound C and Gö6983 remarkably inhibited the promotion by FSE of GLUT4 translocation and expression, but the inhibition effect of Wortmannin was relatively weak ( Figure 4 A,B).…”
Section: Discussionmentioning
confidence: 99%